Inflammatory bowel disease as a risk factor for periodontitis under Taiwanese National Health Insurance Research database - Hui-Chieh Yu; Tsung-Po Chen; Yu-Chao Chang (Elsevier, 2018)
Background/purpose: Inflammatory bowel disease (IBD), comprised Crohn's disease and ulcerative colitis, is a mucosal immune response that affects gastroenterological tract. The association between IBD and periodontitis was inconclusive. In this study, we aimed to investigate the association between IBD and periodontitis by using a register-based dataset. Materials and methods: The dataset conducting in this retrospective cohort study was obtained from the National Health Insurance Research database (NHIRD) in Taiwan. For IBD group, conditionally selected control subjects were matched in 1:4 ratio from general population. The risk of periodontitis among IBD group comparing with non-IBD group was calculated by multivariable Cox proportional hazards model. Results: In IBD cohort, 27 IBD patients (7 Crohn's disease and 20 ulcerative colitis) with catastrophic illness registry were identified. 108 controls were selected as non-IBD cohort. The median follow-up period was 3.00 years in the IBD group and 3.15 years in the non-IBD group. The cumulative incidence of IBD was 4.32 per 100,000 persons. After adjusting for several confounding factors, IBD group had higher risk for developing periodontitis than non-IBD group (adjusted HR: 1.82; 95% CI: 1.09-3.03). To further stratification with subtype, Crohn's disease group had significantly higher risk of periodontitis (adjusted HR: 3.95; 95% CI: 1.59-9.82). Conclusions: Taken together, this retrospective cohort study showed that patients with IBD increase risk of having periodontitis comparing with non-IBD group, especially in Crohn's disease subgroup. Keywords: Periodontitis, Inflammatory bowel disease, Crohn's disease, Ulcerative colitis, Retrospective cohort study, National Health Insurance Research database